Morphologic and quantitative evaluation of preantral follicles of buffalo (Bubalus bubalis) in different reproductive phases - Carvalho, F. C. A. [UNESP]; Oba, Eunice [UNESP]; Leal, L. S. [UNESP] (Pagepress Publ, 2007)
The objectives of the present study were to estimate the population of the normal and degenerated preantral follicles of buffaloes in different reproductive phases and to classify the different types of degeneration of ovarian preantral follicles. For this, 18 ovaries were divided in three groups: prepubertal, non pregnat and pregnant adult females. The ovaries were collected from a slaughterhouse (Frigol - Brazil) and processed for classic histological examination. The follicular population was estimated according to Cahill et al. (1979) and calculated according to Gougeon & Chainy (1987). Young buffaloes, pregnant and non pregnat adults presented an average number of 15.5, 3.7 and 8.9 preantral follicles with normal morphology and type I (the degeneration was observed just in oocyte) and II (oocyte and granulosa cells were degenerated) degeneration, respectively. This experiment demonstrated that the proportions of primordial, primary and secondary follicles were affected by reproductive phase. A significant difference was observed considering the proportions of preantral follicles with normal morphology and Type I degeneration in all reproductive phases evaluated. The primary follicles presented more percentage of Type I degeneration that the others follicles and the primordial and primary follicles presented more percentage of Type II degeneration in three reproductive phases evaluated.
Keywords: Buffaloes; Preantral follicles; Histology